2006
DOI: 10.3892/ijo.28.4.985
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor expression and cell signaling in breast cancer

Abstract: Obesity is considered a risk factor for many cancers, including breast cancer. Our laboratory has previously shown that leptin is mitogenic in many cancer cell lines, including breast. Information regarding the effects of high leptin levels on leptin receptor expression and signaling is lacking. The purpose of this study was to characterize leptin receptor expression in response to leptin in breast cancer cells. In addition, SOCS-3 expression (a leptin inducible inhibitor of leptin signaling), plus MAPK and PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 56 publications
1
66
0
2
Order By: Relevance
“…MAPK and PI3K inhibitors markedly blocked leptin-induced proliferation (42). In human breast epithelial HBL100 cells and human breast carcinoma-derived T-47D cells, leptin increases the expression of phosphorylated STAT3 and P-ERK (31).…”
Section: Discussionmentioning
confidence: 97%
“…MAPK and PI3K inhibitors markedly blocked leptin-induced proliferation (42). In human breast epithelial HBL100 cells and human breast carcinoma-derived T-47D cells, leptin increases the expression of phosphorylated STAT3 and P-ERK (31).…”
Section: Discussionmentioning
confidence: 97%
“…13 Diverse cancer cells derived from different tissues, such as brain, breast, colon or prostate, were reported to have ObR expression. [21][22][23][24][25] Furthermore, Ob-R overexpression not only correlated with the degree of malignancy, but also was an independent prognostic variable to predict poor progression-free survival in brain tumor, ovarian cancer, and breast cancer, 24,26,27 which suggested that ObR+ cells might be closely related with tumor initiation and development. In this study, we claimed that ObR+ glioblastoma cells presented chemoresistance, which showed that TMZ could not inhibit cell proliferation and could not induce apoptosis effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the interplay between Acrp30 and other growth factors has been shown to be important for Acrp30's ability to inhibit cell proliferation (Wang et al, 2005). With respect to breast cancer, and obesity, leptin has been an adipokine implicated in mammary tumorigenesis (Hu et al, 2002;Cleary et al, 2003;Frankenberry et al, 2006;Garofalo et al, 2006). Overweight or obese individuals usually have elevated levels of the growth factor leptin, which is positively correlated to body mass index while Acrp30 is negatively correlated with body mass index.…”
Section: Discussionmentioning
confidence: 99%